A Data-Driven Approach: Integration of Competency Asesmen Kompetensi Madrasah Inonesia (AKMI) in Guidance and Counseling Services in Madrasah - Ishlakhatus Sa'idah; Arinal Haq Fauziah (IAI Miftahul Ulum Pamekasan, 2025)
This study aims to explore how the results of the Indonesian Madrasah Competency Assessment (AKMI) are integrated in the guidance and counselling service system in madrasah. The main focus is to understand the use of information from the AKMI report card by counsellors in designing and implementing more effective interventions and evaluating its impact on the quality of services provided to students. The research method used was a case study with a qualitative approach. Data were collected through observation, in-depth interviews with counsellors, teachers and madrasah head, as well as documentation such as AKMI report cards and guidance notes. Focus group discussions (FGDs) were also conducted to obtain additional perspectives from various parties. Data analysis was done thematically by identifying patterns, themes, and relationships between variables from various data sources. The results show that the integration of AKMI results in guidance and counselling services provides significant benefits, such as personalisation of interventions and more accurate identification of student needs. The IMR data helps in designing more appropriate guidance plans and systematically monitoring student progress. However, the research also identifies challenges such as limited understanding of the use of EMI data and implementation constraints in the field. Positive impacts of using the AKMI report card include improving the quality of guidance and counselling services with a data-driven approach that has the potential to improve students' academic progress and skills. The research recommends further training for counsellors on the use of the AKMI report card as well as the development of tools to support data integration in guidance and counselling services in madrasah.